Hadik Castle in Penzing
Reproduction of photograph of Hadikgasse Castle 62 of Penzing in Vienna. Beethoven stayed in Penzing, at 43 Parkstrasse ("Hadikschlossel"), in May 1824. Clipping from an unidentified publication.